Training of volunteer nurses during the Spanish Civil War (1936–1939): A historical study - López, María; Mirón-González, Rubén; Castro, María-José; Jiménez, José-María (PLOS ONE, 2022)
Background The Spanish Civil War (1936–1939) is an example of a historic event involving nurses, with the participation of professional and volunteer nurses from Spain and other countries. In this context, nurses were trained over short periods of time and recruited to work at hospitals serving the two warring camps. Objectives To identify the characteristics of the training received by volunteer nurses on both sides in the Spanish Civil War and compare it with previous experiences in the history. Design Historical research. Methods Heuristic and hermeneutical analysis of nurse training manuals and news articles from 1936 to 1939. Spanish primary sources were consulted at the Red Cross Documentation Centre Archive in Madrid, the General Military Archive in Ávila, the Municipal Newspaper Archive in Madrid, and the archives of Spanish daily newspapers ABC and La Vanguardia. The following variables were analysed: duration, entry requirements, and theoretical content of the training courses. Consolidated Criteria for Reporting Qualitative Research (COREQ) has been used. Findings Both sides in the conflict offered a varied training programme, which was supported by official institutions and private initiatives. The courses lasted between one week and two months. Entry requirements were influenced by education level, age, moral conduct, health status, and social and political background. Training content focused on the techniques needed in conflict settings and covered specific moral values. Conclusions Despite the different social and political characteristics of the two warring factions, the variety of training programmes on offer, the entry requirements, and the theoretical content of volunteer nurse training were similar on both sides. At the end of the Spanish Civil War, volunteer nurses on the Republican side suffered reprisals or had to go into exile. We now know that some countries involved in World War II provided training courses for volunteer nurses. It would therefore be interesting to ascertain whether Spanish volunteer nurses contributed their experience to these courses.